The healthy migrant effect in primary care - Luis A. Gimeno-Feliu; Amaia Calderón-Larrañaga; Esperanza Diaz; Beatriz Poblador-Plou; Rosa Macipe-Costa; Alexandra Prados-Torres (Elsevier, 2015)
Objective: To compare the morbidity burden of immigrants and natives residing in Aragón, Spain, based on patient registries in primary care, which represents individuals' first contact with the health system. Methods: A retrospective observational study was carried out, based on linking electronic primary care medical records to patients' health insurance cards. The study population consisted of the entire population assigned to general practices in Aragón, Spain (1,251,540 individuals, of whom 12% were immigrants). We studied the morbidity profiles of both the immigrant and native populations using the Adjusted Clinical Group System. Logistic regressions were conducted to compare the morbidity burden of immigrants and natives after adjustment for age and gender. Results: Our study confirmed the "healthy immigrant effect", particularly for immigrant men. Relative to the native population, the prevalence rates of the most frequent diseases were lower among immigrants. The percentage of the population showing a moderate to very high morbidity burden was higher among natives (52%) than among Latin Americans (33%), Africans (29%), western Europeans (27%), eastern Europeans and North Americans (26%) and/or Asians (20%). Differences were smaller for immigrants who had lived in the country for 5 years or longer. Conclusion: Length of stay in the host country had a decisive influence on the morbidity burden represented by immigrants, although the health status of both men and women worsened with longer stay in the host country.